Early Events in Diabetic Retinopathy and Intervention Strategies - Tsin, Andrew T.C; Grigsby, Jeffery G. (IntechOpen, 2018)
The development of diabetic retinopathy is a long slow process affected by hyperglycemia, hypertension, lipid levels and genetics. It is expected that in 20 years' duration nearly all those with diabetes will exhibit diabetic retinopathy. In some patients, it will progress to blindness. While the number of individuals with diabetes increases, our current treatments are only effective at advanced levels of disease. Further, our screening methods to detect those needing treatment are currently not optimal. Early Events in Diabetic Retinopathy and Intervention Strategies covers topics addressing imaging processes currently available in the development of diabetic retinopathy screening. Potential biomarkers, that may be used to identify those at risk and illuminate the new pathways which lead to diabetic retinopathy, are expounded.